Relationship between toxoplasmosis and obsessive compulsive disorder: A systematic review and meta-analysis. - Tooran Nayeri Chegeni; Shahabeddin Sarvi; Afsaneh Amouei; Mahmood Moosazadeh; Zahra Hosseininejad; Sargis A Aghayan; Ahmad Daryani (Public Library of Science (PLoS), 2019)
BACKGROUND:A few studies investigated the relationship between toxoplasmosis and mental disorders, such as obsessive compulsive disorder (OCD). However, the specific nature of the association between Toxoplasma gondii (T. gondii) infection and OCD is not yet clear. The aim of this study was to collect information on the relationship between OCD and toxoplasmosis and assess whether patients with toxoplasmosis are prone to OCD. METHODS:For the purpose of this study, 6 major electronic databases and the Internet search engine Google Scholar were searched for the published articles up to July 30th, 2018 with no restriction of language. The inverse variance method and the random effect model were used to combine the data. The values of odds ratio (OR) were estimated at 95% confidence interval (CI). RESULTS:A total of 9 case-control and 3 cross-sectional studies were included in our systematic review. However, 11 of these 12 articles were entered into the meta-analysis containing 9873 participants, out of whom 389 were with OCD (25.96% positive for toxoplasmosis) and 9484 were without OCD (17.12% positive for toxoplasmosis). The estimation of the random effect model indicated a significant common OR of 1.96 [95% CI: 1.32-2.90]. CONCLUSION:This systematic review and meta-analysis revealed that toxoplasmosis could be as an associated factor for OCD (OR = 1.96). However, further prospective investigations are highly recommended to illuminate the underlying pathophysiological mechanisms of T. gondii infection in OCD and to better investigate the relationship between OCD and T. gondii infection.